If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42x + -1 = 69 + -82 Reorder the terms: -1 + 42x = 69 + -82 Combine like terms: 69 + -82 = -13 -1 + 42x = -13 Solving -1 + 42x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 42x = -13 + 1 Combine like terms: -1 + 1 = 0 0 + 42x = -13 + 1 42x = -13 + 1 Combine like terms: -13 + 1 = -12 42x = -12 Divide each side by '42'. x = -0.2857142857 Simplifying x = -0.2857142857
| 0.9+0.06= | | 4(5x-3)=14x+30 | | 8b+11-36=2b+2 | | 16f-24=16f-32 | | 3x+5=-2x-10whatsx | | 6u-(2u-4)7=3 | | 6(16-4y)=72 | | 5(x-4)-4(x+1)=0 | | 10x-5=9x+8 | | (8x+2)(9x+3)+x=180 | | (8x+2)(9x+3)+x=q | | 5-.66666666n=7 | | 64-7x=11x+18 | | 2x+2=40 | | 8log(x+3)=10 | | 1-3x+8x=3+5x | | 4x+-2=6 | | -16y=0 | | 3(m-9)= | | 3x(x-12)=0 | | (x^2-x+.25)=(.3+x) | | 8-4(m+5)= | | X+2=3x+2-2x | | a^4-12a^2+35=0 | | 6a(2a-1)-(3a^2-3a)= | | -8x=4 | | n-15=30 | | -30-5m=-4(m+7) | | 8x^2-11x+3=0 | | 27=17-2y | | -2=2x+10 | | 26+4a=6a |